My Boss's Daughter - Zucker, David (Pasig City : Viva Video, 2004)
When a young man (Ashton Kutcher) agrees to housesit for his boss (Terence Stamp), he thinks it'll be the perfect opportunity to get close to the woman he desperately has a crush on - his boss's daughter (Tara Reid). But the doesn't plan on the long line of other houseguests that try to keep him from his mission. And he also has to deal with the daughter's older brother, who's on the run from local drug dealer